ANALISIS KOMPARATIF LIMA MODEL PREDIKSI KEBANGKRUTAN: BUKTI EMPIRIS DARI PT MATAHARI DEPARTMENT STORE TBK - Rakhmat Hadi Sucipto; Rosmita Rosmita; Helmy Ivan Taruna (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to detect financial distress at PT Matahari Department Store Tbk by comparing five widely used bankruptcy prediction models: Altman Z-Score, Springate S-Score, Grover G-Score, Zmijewski X-Score, and Ohlson O-Score. Using PT PT Matahari Department Store Tbk’s financial data, independent samples t-tests and Cohen’s d effect sizes were employed to assess significant differences among models. The Springate, Grover, and Ohlson models produced identical predictions, with the company facing bankruptcy from 2015 to 2025. Altman produced nearly identical results, except for 2016 and 2017, with a gray prediction. Zmijewski produced the most striking difference, with seven years in the safe category and four years in the bankruptcy zone. Results indicate that Altman, Springate, Grover, and Zmijewski do not differ significantly (p > 0.05), suggesting convergence among MDA-based and probit models. In contrast, Ohlson differs significantly from all four models (p < 0.001) with very large effect sizes (d = 1.96–4.24), reflecting the logit paradigm’s sensitivity to leverage and firm size. The Springate–Grover pair also differs significantly (p = 0.001; d = 1.76). Levene’s test reveals heterogeneity of variances in five pairs, warranting Welch’s correction. Theoretically, the findings support a contingency approach to model selection, while practically, they recommend triangulation of the four MDA models and complementary use of Ohlson as an early warning system.